Preventive effects of enoxaparin and hesperidin in cerulein-induced acute pancreatitis in rats - YÜKSEL, MERAL (AVES, 2013)
Background/aims: Acute pancreatitis accounts for almost 250.000 hospital admissions annually in the United States. Most promising treatment approaches are preventive; however, little is known about the early factors initiating acute pancreatitis. We aimed to evaluate the preventive effects of enoxaparin and hesperidin in cerulein-induced acute pancreatitis. Patients and methods: We used 70 Wistar albino rats for this study. Rats were divided into 7 groups: control group, and groups that were administered cerulein (Group 2), enoxaparin (Group 3), hesperidin (Group 4), cerulein with enoxaparin (Group 5), cerulein with hesperidin (Group 6), and cerulein with both enoxaparin and hesperidin (Group 7). Edema formation; leukocyte infiltration; measurement of the amylase level, pancreatic tissue weight, and pancreatic tissue oxidative capacity; and chemiluminescence using luminol, lucigenin, and nitric oxide levels as indices of tissue oxidative capacity were used to evaluate pancreatitis. Results: Acute edematous mild pancreatitis was induced in groups 2, 5, and 6 by cerulein injections. Enoxaparin and hesperidin significantly decreased (p <0.001) all the tested parameters in these rats. Enoxaparin and hesperidin did not offer complete protection but showed 50% decrease in edema formation. The preventive agents showed no superiority to each other. Further, when enoxaparin and hesperidin were used in combination, no significant additive effects with regard to anti-inflammatory and anti-oxidative actions were present. Conclusion: We showed that both enoxaparin and hesperidin exerted significant preventive effects in all the parameters related to acute pancreatitis in our experimental rat model.
Keywords: Acute pancreatitis; enoxaparin; hesperidin; PURIFIED FLAVONOID FRACTION; NECROTIZING PANCREATITIS; FREE-RADICALS; COAGULATION; HEPARIN; MICROCIRCULATION; INFLAMMATION; PROTEINS